Effects of Heat Treatment Temperatures on the Performance of Au/TiO2 Catalyst for Liquid Phase Selective Hydrogenation of Phthalic Anhydride - Liu, Yingxin; Xing, Tiefeng (Asian Journal of Chemistry, 2012)
A series of Au/TiO2 catalysts with the same gold loading were prepared by deposition-precipitation method followed by calcination and reduction at different temperatures and applied into the hydrogenation of phthalic anhydride. The effects of heat treatment temperatures on their performances were investigated. It was observed that higher calcination temperature and reduction temperature led to an increase in the gold particle size and a collapse of mesoporous structure, which was accompanied by the decrease in the catalytic performance. Among the Au/TiO2 catalysts investigated, the one calcined at 300 ºC and reduced at 200 ºC, with smaller gold particle size (3.1 nm), exhibited the best catalytic performance with 94.7 % conversion and 94.2 % selectivity to phthalide.